Is Everything Everywhere? Dispersal Limitation Impacts Methanotroph Community Functioning - Jie Fang; Yongcui Deng; Zihao Liu; Jonathan M. Adams (Environmental Microbiology, 2025)
The significance of dispersal limitation in microbial ecology and biogeography remains debated. We aimed to clarify the role of dispersal limitation in the adaptation of methanotroph communities to salt‐stress, essentially testing the ‘everything is everywhere’ hypothesis in functional terms. Riparian sediments along the Yangtze River and lakeshore sediments at varying geographical distances inland from the river were collected. Microcosms were incubated with ~5% CH 4 under three conditions: 50 g/L salinity, 50 g/L salinity plus a methanotroph community inoculum, and a control. We observed a significant delay in methane oxidation at increased salinity, but salt‐tolerant methanotrophic activity persisted in riparian sediments. Using DNA‐SIP, we identified halotolerant Methylobacter ‐taxa that possibly dispersed from the saline estuary. By contrast, in lakes/ponds inland away from the Yangtze, progressively fewer samples oxidised methane under high salinity without inoculation, until at 130 km distance, no samples could adapt. Methanotrophy was restored in every case by inoculation with propagules from the saline Yangtze Delta, confirming the impact of dispersal limitation of halotolerant Methylobacter ‐propagules in constraining ecosystem functional adaptation. By focusing on ecosystem functions rather than just taxonomic communities, this study uniquely tests a key paradigm in microbial ecology, suggesting that broad‐scale microbial dispersal limitation can constrain ecosystem adaptation.